(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
The article explores the historical formation, evolutionary stages, and continuous development of the piano as one of the most expressive and versatile musical instruments. It highlights the piano’s origins from early keyboard instruments such as the monochord, clavichord, and harpsichord, emphasizing Bartolomeo Cristofori’s innovative role in creating the first piano. The study traces how the piano evolved technically and artistically through various periods — from the classical works of Mozart and Beethoven to the virtuosic expressions of Liszt and Chopin, and finally to the emergence of electronic and digital pianos in the 20th century. The article concludes that the piano stands as a unique synthesis of human intellect, technological progress, and artistic spirit, maintaining its central role in musical performance, education, and creativity across centuries.